Impact of Hospital Care Environment on Patient Mortality and Nurse Well-being - Hind nafea alrashidi,Fawzah Mezel Alanazi Aminah Shayhan Aldafery,Hasen Hamis alruwaili Abeer saad alrashidi, Muneefa Nafea alrashidi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study aimed to investigate the comprehensive impacts of nurse practice environments on both nurse and patient outcomes, while considering the influence of nurse staffing and education. Background: While the associations between staffing, education, and patient outcomes are well-established, research on the impact of care environments on outcomes has been relatively limited. Methods: Data from 10,184 nurses and 232,342 surgical patients ش were examined. Care environments were assessed using the practice environment scales of the Nursing Work Index. Outcomes included nurse job satisfaction, burnout, intent to leave, perceptions of care quality, as well as patient mortality and failure to rescue. Results: Nurses reported higher job satisfaction and fewer concerns regarding care quality, while patients exhibited significantly reduced risks of mortality and failure to rescue in hospitals with better care environments. Conclusion: Optimizing care environment factors alongside nurse staffing and education is crucial for achieving high-quality care.